Ultrasensitive plano-concave optical microresonators for ultrasound sensing. Issue 11 (November 2017) - Guggenheim, James; Li, Jing; Allen, Thomas; Colchester, Richard; Noimark, Sacha; Ogunlade, Olumide; Parkin, Ivan; Papakonstantinou, Ioannis; Desjardins, Adrien; Zhang, Edward; Beard, Paul
Abstract Highly sensitive broadband ultrasound detectors are needed to expand the capabilities of biomedical ultrasound, photoacoustic imaging and industrial ultrasonic non-destructive testing techniques. Here, a generic optical ultrasound sensing concept based on a novel plano-concave polymer microresonator is described. This achieves strong optical confinement (Q -factors > 105 ) resulting in very high sensitivity with excellent broadband acoustic frequency response and wide directivity. The concept is highly scalable in terms of bandwidth and sensitivity. To illustrate this, a family of microresonator sensors with broadband acoustic responses up to 40 MHz and noise-equivalent pressures as low as 1.6 mPa per √Hz have been fabricated and comprehensively characterized in terms of their acoustic performance. In addition, their practical application to high-resolution photoacoustic and ultrasound imaging is demonstrated. The favourable acoustic performance and design flexibility of the technology offers new opportunities to advance biomedical and industrial ultrasound-based techniques. An optical-based scheme for ultrasound sensing provides very high sensitivity with excellent broadband acoustic frequency response and wide directivity.